Functional Outcome in Endoprosthetic Replacement around the Knee: A Narrative Review - Eyesan, Uwale Samuel; Idowu, Oluwaseyi Kayode (Nigerian Journal of Orthopaedics and Trauma, 2020)
In general, most comparative studies have reported that successful limb salvage surgeries have better functional outcomes than amputations. This is largely due to the advances in surgical techniques and adjuvant therapy which allows reconstruction such as endoprosthetic replacements (EPR). Clinician‑reported outcome measures and patient‑reported outcome measures have been utilised to evaluate the benefits of orthopaedic surgical procedures. The most widely used measures in the field of orthopaedic oncology are the Musculoskeletal Tumour Society Score and the Toronto Extremity Salvage Score. The Jury is still out on the evidence basis for the functional outcome of EPR, especially around the knee joint. There is a need for more randomised control trials, systematic reviews or meta‑analyses to critically appraise and formally synthesise the best available evidence to provide a statement of conclusion on the functional outcome of EPRs.